Cytochrome P450 monooxygenases. - Wong, L (1998)
The field of P450 research is progressing rapidly. The active sites of structurally characterized bacterial P450 enzymes have been rationally re-engineered to alter both substrate specificity and selectivity of substrate oxidation. Many human P450 enzymes have been functionally expressed and new methods of substrate turnover described. These developments, arising from our increased understanding of the chemistry and molecular biology of P450 enzymes, open up new and exciting research directions.